A Hybridized Finite Taylor Formula by Fluctuation Free Remainder Term for a Multivariable Function Approximation - (:unkn) unknown (AMER INST PHYSICS, 2009)
Based on the Taylor's Theorem for functions of several variables, a new formulation is developed here to approximate the remainder term of the Multivariate Taylor polynomial by means of the recently developed Fluctuation Theorem. This new formulation is tested on functions of two variables.
Keywords: Approximation Methods; Multivariate Taylor's Theorem; Explicit Remainder Term; Fluctuation Expansion